Temperature Effects on Quantum Ballistic Transport in Double-Gate MOSFETs Using Landauer"“BÃ¼ttiker Formalism - Sangian, Messiah Charity; Syuhada, Ibnu; Khairurrijal, Khairurrijal; Noor, Fatimah Arofiati (POSITRON, 2025)
This paper presents the development and application of a simulator utilizing the Landauer"“BÃ¼ttiker formalism to model quantum ballistic transport in double-gate (DG) metal-oxide-semiconductor field-efffect transistors (MOSFETs), focusing on temperature variations from 0.9 K to 300 K. The simulator employs advanced modelling techniques, including the exponential decay model, quantum interference model, and the Wentzel"“Krames"“Brillouin (WKB) approximation for transmission probability. Additionally, it incorporates the Landauer"“BÃ¼ttiker approach for current calculation and the gradual channel approximation (GCA) model for device operation. By leveraging these techniques, the simulator provides comprehensive insights into the quantum mechanical effects that influence device performance under various thermal conditions. This research underscores the critical role of temperature variations in the design and optimization of DG MOSFETs, emphasizing the necessity of effective thermal management and a thorough understanding of quantum effects to enhance the performance and reliability of nanoscale transistor technologies. These findings highlight the importance of incorporating temperature-dependent quantum mechanical considerations in advancing future nanoelectronic devices.